Pengaruh Pelatihan, Motivasi dan Lingkungan Kerja terhadap Kinerja Pegawai Badan Pendapatan Daerah Kabupaten Jember - Dzicko Ardianto Priyadi; Toni Herlambang; Wenny Murtalining Tyas (International Forum of Researchers and Lecturers, 2026)
This study aims to examine and analyze the effect of training, motivation, and work environment on employee performance at the Regional Revenue Agency (BAPENDA) of Jember Regency. The background of this research is based on the low achievement of Regional Original Revenue (PAD) targets, gaps in training implementation that have not been based on specific needs, variations in employee motivation, and work environment conditions that are not yet fully optimal. This study employs a quantitative approach. The population and sample consisted of all 125 employees of BAPENDA Jember Regency, selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the SPSS program. The results indicate that training has no significant effect on employee performance, with a t-value of 1.099, regression coefficient β = 0.063, and sig. 0.274 > 0.05; motivation has no significant effect on employee performance, with a t-value of −0.664, regression coefficient β = −0.036, and sig. 0.508 > 0.05; work environment has a positive and significant effect on employee performance, with a t-value of 8.939, regression coefficient β = 0.677, and sig. < 0.001. Simultaneously, the three variables explain 57.3% of the variation in employee performance (R² = 0.573), with the remaining 42.7% explained by other factors outside the model.